Assessment of occupational congruence on occupational satisfaction of graduates in Kenya - Waruita, Ann Gathigia; Gitonga, Ciriaka Muriithi; Atitwa, Edwin Benson (Journal of Education and Learning (EduLearn), 2025)
Graduates in mismatched careers with their personalities often feel dissatisfied and less productive. This research aims at assessing occupational congruence and occupational satisfaction of graduates in Kenya, informed by Holland’s theory. Objective of the study is to investigate the mediating effect of congruence on the relationship between Holland’s personality types and occupational satisfaction. A longitudinal cohort research design was adopted, involving participants from a 2012 study, with 76 respondents participating. Data was collected using Holland's Self-Directed Search (SDS) 4th Edition questionnaire and an interview schedule. Logistic regression was used to examine the mediating effect of congruence on the relationship between personality types and occupational satisfaction. Results indicated that the mediating effect of congruence was statistically significant at (p0.05). This study provides additional empirical evidence for the educational institutions, career counsellors, and employers for policy making. Additionally, Holland’s classification tool can be used for career guidance to align students with suitable academic fields and ensure congruence of learners with academic programmers, and that of employees with their careers resulting to employee satisfaction.